Deforestation and Land Conversion: A deep dive into Malaysia - Wen Nee An (Budi Luhur Journal of Strategic & Global Studies, 2024)
Abstrak: Dengan pesatnya pertumbuhan Malaysia sebagai negara berkembang, urbanisasi dan perluasan pertanian telah menjadi elemen kunci yang berkontribusi signifikan terhadap penggundulan hutan dan alih fungsi lahan di wilayah tersebut. Akibatnya, banyak dampak dari penyebab ini muncul dengan cepat dalam beberapa tahun terakhir, seperti erosi tanah dan perubahan iklim. Untuk mengatasi masalah lingkungan ini secara komprehensif, reboisasi, keterlibatan organisasi nonpemerintah dalam masalah ini, dan promosi skema sertifikasi oleh pemerintah Malaysia dapat dilihat sebagai strategi mitigasi.   Abstract:  This paper discusses the issue of deforestation and land conversion and the challenges that arise in Malaysia. With the rapid growth of Malaysia as a developing country, urbanisation and agricultural expansion have been the key elements that significantly contribute to deforestation and land conversion in the region. As a result, many effects of this cause have been quickly emerging in recent years, such as soil erosion and climate change. In order to comprehensively overcome this environmental problem, reforestation, involvement of non-governmental organisations in this issue and promotion of certification schemes by the Malaysian government can be seen as mitigation strategies.